Amelioration of Saline Stress on Chia (Salvia hispanica L.) Seedlings Inoculated With Halotolerant Plant Growth-Promoting Bacteria Isolated From Hypersaline Environments - Yañez-Yazlle, María Florencia; Romano-Armada, Neli; Rajal, Verónica Beatriz; Irazusta, Verónica Patricia (Frontiers in Agronomy, 2021)
The rhizosphere and microbiome of halotolerant plants could be crucial for alleviating salinity stress during plant growth. The aims of this work were: (1) to isolate bacteria from rhizosphere and bulk soil samples from the Salar del Hombre Muerto (Catamarca, Argentina), (2) to characterize different plant growth-promoting (PGP) activities produced by these bacterial isolates, and (3) to evaluate their effect on the initial growth of chia (Salvia hispanica L.) under saline stress. A total of 667 microorganisms were isolated using different culture media with NaCl, and their abilities for nitrogen fixation, phosphate solubilization, siderophores production, and indole-3-acetic acid (IAA) production were evaluated. Thirteen strains were selected for showing all the tested PGP activities; they belonged to the genera Kushneria, Halomonass, Pseudomonas, Planomicrobium, and Pseudarthrobacter. The strains Kushneria sp. and Halomonas sp. showed the highest salinity tolerance (from 50 to 2000 mM NaCl) and biomass and biofilm production. Chia seeds were treated with six of the first thirteen selected strains to evaluate their plant growth-promoting effect under saline stress (without and with 50 and 100 mM NaCl). Halomonas sp. 3R.12 and Kushneria sp. T3.7 produced heavier seedlings with a balanced shoot/root length ratio, while Pseudomonas sp. AN23 showed the best effect upon chia seedlings, with a morphological response similar to non-stressed seedlings. On the other hand, seedlings displayed no responses when inoculated with Planomicrobium sp. 3S.31 and Pseudarthrobacter sp. ER25. This study contributes to the knowledge on microorganisms from hypersaline environments as plant growth promoters for their use in the production of salt-sensitive crops, among other potential uses.